Factors Affecting Cultural Normalization from the Perspective of the Holy Quran - Sayyed Mohsen Mir Sondosi (آموزه‌های قرآنی)
Many cultural foundations in any micro or macro society include values and norms that shape the orientation of attitudes, mindsets, and behaviors among them. The original and ideal culture of Islam, which is manifested in the Holy Quran, has paid special attention to the expression of transcendent norms and values for happiness in individual and social life. From this point of view, the ideal society of Islam is the society that can provide the ground for the realization of these values and norms among Muslims as much as possible, and thus guarantee their happiness in this world and the hereafter. The establishment of desirable religious values and norms in the Muslim community depends on a set of factors that lack of timely and appropriate attention to them not only interferes with the realization of religious culture but also facilitates the entry and acceptance of values and patterns that often conflict with values and norms of Islam that wants. This article tries to address the main factors that, from the Qur'an’s point of view, create and spread the culture and norms that are desirable and desired by Islamic law, and as a result, the Muslim community becomes normal. These factors include the three main categories of norm sending, norm itself and normative audience (target group), which we will briefly introduce the effectiveness features of each based on Quranic verses and references.